2017
DOI: 10.5897/ajmr2017.8685
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aspergillus and Fusarium ear rot causative fungi in soils under push-pull and maize monocropping system in Western Kenya

Abstract: It is imperative to establish the distribution and density of soil fungal communities as a requisite for formulating strategies for management of ear rot infections and mycotoxin contamination. In a two seasons study, short (SR) and long rainy (LR) seasons, we investigated the distribution of Aspergillus and Fusarium fungi causing ear rots and producing mycotoxins from 120 soil samples collected from maize fields under push-pull (PP) and maize monocrop (MM) systems in Western Kenya. Cultural methods were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Indeed, reports of lower mycotoxin producing fungi in push-pull plots where Desmodium spp. are used as intercrops (Maxwell et al, 2017; Owuor et al, 2018; Njeru et al, 2020) as well as associational resistance in maize grown on soil from long term push-pull fields (Mutyambai et al, 2019) may be the first clue about the important role of Desmodium spp. in shaping soil microbial communities leading to diverse ecological benefits related to food production and safety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, reports of lower mycotoxin producing fungi in push-pull plots where Desmodium spp. are used as intercrops (Maxwell et al, 2017; Owuor et al, 2018; Njeru et al, 2020) as well as associational resistance in maize grown on soil from long term push-pull fields (Mutyambai et al, 2019) may be the first clue about the important role of Desmodium spp. in shaping soil microbial communities leading to diverse ecological benefits related to food production and safety.…”
Section: Resultsmentioning
confidence: 99%
“…were found in high abundance in soils of maize monoculture compared to long-term push-pull farms that employed Desmodium intercrops (Mwakilili et al, 2021). Similarly, (Maxwell et al, 2017) reported lower frequency of Aspergillus flavus in maize cobs from monoculture plots than in Desmodium intercropping push-pull systems, but an opposite trend for A. parasiticus. It is possible that the soils of the area are rich in these fungal taxa and the time under Desmodium spp.…”
Section: Composition and Abundance Of Soil Microorganismsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is because the soil is an essential habitat for mycotoxigenic fungi species such as Aspergillus and Fusarium spp. [21]. A similar study [20] reported that 37.6% and 39.1% of the farmers in Nandi and Makueni counties, respectively, were not drying maize on a canvas instead they were drying their unshelled maize directly on the ground.…”
Section: Drying Of Grainsmentioning
confidence: 94%